Reduced intraepidermal nerve fibre density, glial activation, and sensory changes in HIV type-1 Tat-expressing female mice: involvement of Tat during early stages of HIV-associated painful sensory neuropathy. (May 2018) - Wodarski, Rachel; Bagdas, Deniz; Paris, Jason J.; Pheby, Tim; Toma, Wisam; Xu, Ruqiang; Damaj, M. Imad; Knapp, Pamela E.; Rice, Andrew S.C.; Hauser, Kurt F.
Abstract: Introduction: HIV infection is associated with chronic pain states, including sensory neuropathy, which affects greater than 40% of patients. Objectives and Methods: To determine the impact of HIV-Tat induction on nociceptive behaviour in female mice conditionally expressing HIV Tat1-86 protein through a doxycycline (DOX)-driven glial fibrillary acidic protein promoter, intraepidermal nerve fibre density and immune cell activation in the dorsal root ganglion (DRG) and spinal cord were assessed by immunohistochemistry. Mice were assessed for mechanical and thermal sensitivity for 9 weeks using von-Frey and Hargreaves tests. Results: Intraepidermal nerve fibre density was significantly reduced after 6 weeks of Tat induction, similar to sensory neuropathy seen in clinical HIV infection. Tat induction through DOX caused a significant reduction in paw withdrawal thresholds in a time-dependent manner starting the 4th week after Tat induction. No changes in paw withdrawal latencies were seen in Tat(−) control mice lacking the tat transgene. Although reductions in paw withdrawal thresholds increased throughout the study, no significant change in spontaneous motor activity was observed. Spinal cord (cervical and lumbar), DRG, and hind paw skin were collected at 8 days and 6 weeks after Tat induction. HIV-Tat mRNA expression was significantly increased in lumbar DRG and skin samples 8 days after DOX treatment. Tat induced a significant increase in the number of Iba-1 positive cells at 6 weeks, but not after 8 days, of exposure. No differences in glial fibrillary acidic protein immunoreactivity were observed. Conclusion: These results suggest that Tat protein contributes to painful HIV-related sensory neuropathy during the initial stages of the pathogenesis. Abstract : Supplemental Digital Content is Available in the Text.